2002
DOI: 10.1023/a:1021873411611
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: 1. Central serotonergic dysfunction and genetic factors are associated with suicidal behavior in psychiatric patients. The goal of this study was to examine the association between the 5-HT2A gene polymorphism (102T/C) and suicide in a sample of Brazilian psychiatric inpatients. 2. We studied 225 subjects. Genotypic frequencies were obtained after DNA extraction and the region of 5-HT2A/T102C containing the polymorphic site amplified by the polymerase chain reaction and digested with the restriction enzyme Hpa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
1
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 13 publications
0
2
1
1
Order By: Relevance
“…These results reported here in a Chinese population were not in agreement with those reported by Dawei Li, who found no association of the T102C polymorphism with either schizophrenia or suicidal behavior, evidence of significant association was only detected between the A-1438G polymorphism and suicidal behavior [30]. Our results failed to confirm previous reports that genotype frequencies of 102 T/C 5-HT 2A receptor gene polymorphism in mood disorders do not differ from healthy volunteers [31-33]. Moreover, Ho-kyoung Yoon concluded that the 5-HT 2A T102C polymorphism may not be associated with susceptibility to suicidal behavior in Korean population [34].…”
Section: Discussioncontrasting
confidence: 99%
“…These results reported here in a Chinese population were not in agreement with those reported by Dawei Li, who found no association of the T102C polymorphism with either schizophrenia or suicidal behavior, evidence of significant association was only detected between the A-1438G polymorphism and suicidal behavior [30]. Our results failed to confirm previous reports that genotype frequencies of 102 T/C 5-HT 2A receptor gene polymorphism in mood disorders do not differ from healthy volunteers [31-33]. Moreover, Ho-kyoung Yoon concluded that the 5-HT 2A T102C polymorphism may not be associated with susceptibility to suicidal behavior in Korean population [34].…”
Section: Discussioncontrasting
confidence: 99%
“…One of the most remarkable single nucleotide polymorphisms of the 5HTR2A gene is T102C (rs6313). Several genetic studies have shown an association between 5HTR2A and suicidal behavior [17,18]. Similarly, this common variant has been studied not only in relation to suicidal behavior, but also in association with other diseases such as schizophrenia [19-21], alcoholism [22], and depression [23].…”
Section: Introductionmentioning
confidence: 99%
“…Таким образом, в соответствии с полученными результатами полиморфизм T102C гена 5-HTR2A связан с суицидальным поведением. Несколько других исследований также показали связь между геном 5-HTR2A и суицидальным поведением [6,9], указав на заметное увеличение риска суицидального поведения у носителей аллеля С для полиморфизма T102C гена 5-HTR2A. Тем не менее авторы проведенного в 2013 г. мета-анализа опровергают наличие какой-либо связи гена рецептора серотонина типа 2А с суицидальностью [5].…”
Section: таблицаunclassified